Absolute instability of double annular jets: local stability analysis (Archives of Mechanics - Test, 2021)
The paper presents the local linear stability analysis of the double annular jets. The calculations show that the first absolutely unstable helical mode can be generated in the non-swirling annular jets by the back-flow in the central recirculation zone or sufficiently strong back-flow in the external recirculation zone. The influence of the back-flow magnitude on the frequency, growth rate and eigenfunctions of the first helical mode is discussed. The calculations are completed with an analysis of the influence of the swirl intensity in the internal and external jets on the characteristics of the first absolutely unstable helical mode.